2009
DOI: 10.1016/j.neulet.2009.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-2 deficiency-induced T cell autoimmunity in the mouse brain

Abstract: Interleukin-2 (IL-2) has been implicated in the pathogenesis of neurodevelopmental and neurodegenerative disorders. Studies from our lab have shown that adult IL-2 knockout (KO) mice exhibit septohippocampal pathology and related behavioral deficits. Compared to IL-2 wild-type (WT) mice, IL-2 KO mice have a marked and selective loss of septal cholinergic neurons that occurs between the third postnatal week and adulthood. Given that the development of septal neurons is completed by embryonic day 17 and that IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
24
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 29 publications
4
24
1
4
Order By: Relevance
“…Brain cells also produced IL-2 [10, 17, 22]. Our research indicates that loss of brain IL-2 gene expression may play a pivotal role in altering the endogenous neuroimmunological mellieu and the development of CNS autoimmunity, effects that mirror IL-2’s actions in the peripheral immune system (e.g., regulatory T cell function, self-tolerance) [4, 6, 12, 14]. Thus, dysregulation of IL-2 expression in the peripheral immune system and the brain may have important implications for identifying injury-induced neuroimmunological processes that drive responses towards either CNS neurodegeneration or neuroregeneration.…”
mentioning
confidence: 99%
“…Brain cells also produced IL-2 [10, 17, 22]. Our research indicates that loss of brain IL-2 gene expression may play a pivotal role in altering the endogenous neuroimmunological mellieu and the development of CNS autoimmunity, effects that mirror IL-2’s actions in the peripheral immune system (e.g., regulatory T cell function, self-tolerance) [4, 6, 12, 14]. Thus, dysregulation of IL-2 expression in the peripheral immune system and the brain may have important implications for identifying injury-induced neuroimmunological processes that drive responses towards either CNS neurodegeneration or neuroregeneration.…”
mentioning
confidence: 99%
“…ИЛ2 экспрессируется как клетками иммунной системы, так и клетками головного мозга, оказывает влияние на электрофизиологическую функцию нейронов, возбуждая реактивность нейронов гипоталамуса и коры головного мозга, регулирует экс-прессию генов в клетках гипофиза, активирует парасим-патический отдел вегетативной нервной системы [37]. В экспериментальных моделях показано, что дефицит ИЛ2 приводит к повышению продукции нескольких про-воспалительных цитокинов, нарушает архитектонику гиппокампа и связан с нарушением поведения у взрослых мышей [41,42].…”
unclassified
“…IL-2 receptors are enriched in the septohippocampal system where the cytokine has been shown to have trophic effects on fetal septal and hippocampal neurons, and have potent effects on acetylcholine release from septohippocampal cholinergic neurons [1, 11, 22, 23, 26]. In addition to IL-2’s actions in the immune and central nervous systems, we have found that loss of brain IL-2 gene expression results in dysregulation of the brain’s endogenous neuroimmunological milieu (e.g., alterations in the normal balance of cytokines and chemokines), and that such effects may be involved in initiating processes that lead to central nervous system (CNS) autoimmunity [4, 1315]. …”
mentioning
confidence: 99%
“…Neuroimmunology studies revealed that T lymphocytes can have important effects on CNS neurons, and normal peripheral T cell function has been found to be essential for the preservation of the phenotype of injured motoneurons [7, 16, 25]. We previously found in IL-2KO mice that there is a marked infiltration of T cells to the brain that mirrors, in relative magnitude, the progression of autoimmunity in the periphery [13]. In the present study, we sought to test the hypothesis that the loss of quantifiable medial septal cholinergic neurons in IL-2KO mice is due to the loss of cholinergic phenotype rather than neuronal cell loss, and that the loss of phenotype is due to loss of brain-derived IL-2 rather than changes in neuroimmune status or T cell infiltration.…”
mentioning
confidence: 99%
See 1 more Smart Citation